2005
DOI: 10.1109/temc.2005.857362
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Investigation of the Resonance Damping Performance of Magnetic Material Coating in Power/Ground Plane Structures

Abstract: Power bus structure, consisting of two parallel solid power and ground planes separated by an insulator, behaves as a cavity resonator at high frequencies. Noise on the power bus, due to a sudden change in the current drawn by an active component, can appear as an undesired spatial fluctuation in the voltage between power and ground, especially at resonant frequencies of the resultant cavity, which may lead to problems in signal integrity, excessive delays, false switching, and radiated emission. These resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Earlier studies have shown that by using lossy materials to absorb the electromagnetic energy in the resonant cavity, the resonance phenomenon could be damped to some degree and the SE near resonant frequencies could be improved. [15][16][17][18] In Ref. [15], it was experimentally verified that the SE near resonance frequencies could be enhanced by placing a layer of lossy dielectric material in the back of an enclosure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that by using lossy materials to absorb the electromagnetic energy in the resonant cavity, the resonance phenomenon could be damped to some degree and the SE near resonant frequencies could be improved. [15][16][17][18] In Ref. [15], it was experimentally verified that the SE near resonance frequencies could be enhanced by placing a layer of lossy dielectric material in the back of an enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…[15], it was experimentally verified that the SE near resonance frequencies could be enhanced by placing a layer of lossy dielectric material in the back of an enclosure. Reference [16] shows that the resonance noise from a power bus structure can be suppressed by coating the power and ground planes with a thin layer of lossy magnetic material. In Ref.…”
Section: Introductionmentioning
confidence: 99%